Factors affecting third‐stage management and postpartum hemorrhage in planned midwife‐led home and birth center births in the United States. Issue 4 (29th July 2020) - Erickson, Elise N.; Bovbjerg, Marit L.; Cheyney, Melissa J.
Abstract: Background: Postpartum hemorrhage (PPH) is a potential childbirth complication. Little is known about how third‐stage labor is managed by midwives in the United States, including use of uterotonic medication during community birth. Access to uterotonic medication may vary based on credentials of the midwife or state regulations governing midwifery. Methods: Using data from the Midwives of North America 2.0 database (2004‐2009), we describe the PPH incidence for women giving birth in the community, their demographic and clinical characteristics, and methods used by midwives to address PPH. We also examined PPH rates by midwifery credentials and by the presence of regulations for legal midwifery practice. Results: Of the 17 836 vaginal births, 15.9% had blood loss of over 500 mL and 3.3% had 1000 mL or greater blood loss. Midwives used pharmaceuticals to prevent or treat postpartum bleeding in 6.3% and 13.9% of births, respectively, and the rate of hospital transfer after birth was 1.4% (n = 247). In adjusted analyses, PPH was less likely when births occurred at home vs a birth center, if the midwife had a CNM/CM credential vs a CPM/LM/LDM credential, or if the woman was multiparous without a history of PPH or prior cesarean birth. PPH was more likely in states with barriers to midwifery practice compared with regulated states (OR: 1.26; 95% CI, 1.16‐1.38). Conclusions: Women giving birth in the community experienced low overall incidence of PPH‐related hospital transfer. However, the occurrence of PPH itself would likely be reduced with improved legal access to uterotonic medication.